Architectural photogrammetry for the recording of heritage buildings: an overview - Salleh, Nurul Hamiruddin (IIUM Press, 2012)
In heritage documentation, recording techniques can be divided into two broad categories, namely photographic and non-photographic methods. Photographic methods include a photographic image is fundamental to the whole recording process, such as computer-rectified photography, photogrammetry and laser scanning. Whereby, non- photographic methods are including hand survey and theodolite-based measurements. Three main criteria should be considered when making decisions about the specification of the recording: the cost, technical considerations or logistics and, finally, whether the survey will fulfil the technical and academic requirements and be understood by the end user. Moreover, the choice of the most appropriate and reliable recording methods will depend on the scale and type of building, level of accuracy, and level of recording needed. This paper discusses the application of photogrammetry techniques in the recording of heritage buildings. The principles, accuracy and challenges of the technique are also described.